Neoadjuvant Therapy for Neuroendocrine Neoplasms: Recent Progresses and Future Approaches - Lania, Andrea; Ferraù, Francesco; Rubino, Manila; Modica, Roberta; Colao, Annamaria; Faggiano, Antongiulio (Frontiers in Endocrinology, 2021)
Even if neuroendocrine neoplasms (NENs) are considered rare, their incidence has rapidly increased in the last few decades. NENs are a heterogeneous group of tumors, their treatment being challenging and requiring a multidisciplinary approach. Though the only curative treatment is surgery, up to 50% of patients are diagnosed with metastatic disease. These patients can be offered long-term systemic treatment (e.g. somatostatin analogs, the mTOR inhibitor everolimus, the tyrosine kinase inhibitor sunitinib, and peptide receptor radionuclide therapy, alone or combined with cytoreductive procedures) to obtain both symptoms control and tumor growth inhibition. In the last years, neoadjuvant chemo(radio)therapy has become part of the standard of care in the treatment of different cancer types. However, evidence of its efficacy and safety in NEN patients has not yet been confirmed in the literature. The aim of the present review is to perform an extensive review of the scientific evidence for neoadjuvant therapy in patients with gastroenteropancreatic and thoracic NENs.